Diversity of Ferns (Pteridophyta) in Ancient Volcano Mount Nglanggeran Climbing Track and the Booklet Development for Independent Learning Sources - Averos, Iqbal Fajrin; Widodo, Widodo; Widiyatami, Cahya Arsyi; Utami, Wuri Esti Tyas (Proceeding International Conference on Science and Engineering, 2019)
This study aims to determine the diversity of ferns species in Ancient Volcano Mount (Gunung Api Purba) Nglanggeran climbing track and develop the Ferns Booklet as a source of students' independent learning as well as knowing the quality of the product. This type of research is development research (R & D) using three stages. The first is taking sampling and identification, second is developing product and the last is trials product. The product was evaluated and validated by material experts, media experts, and 5 peer reviewers. A limited test was conducted by a biology teacher and 15 students of MA Wahid Hasyim Sleman (Islamic Senior High School) by questionnaire method. The results showed that ferns diversity has 39 species by 20 genera in 12 families. Qualitative data from the results are converted into quantitative data. Product quality according to the assessors is in the very good category, with an ideal percentage assessment from the experts, peer reviewers, biology teachers and students respectively 87.59%; 86.48%; 84.83%; and 90.88%. Thus, the Fern Booklet is very suitable to be used as a source of independent learning students.